2015
DOI: 10.1016/j.jaci.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 and leukotriene E4 synergize to stimulate diverse TH2 functions and TH2 cell/neutrophil crosstalk

Abstract: BackgroundProstaglandin D2 (PGD2) and cysteinyl leukotrienes (cysLTs) are lipid mediators derived from mast cells, which activate TH2 cells. The combination of PGD2 and cysLTs (notably cysteinyl leukotriene E4 [LTE4]) enhances TH2 cytokine production. However, the synergistic interaction of cysLTs with PGD2 in promoting TH2 cell activation is still poorly understood. The receptors for these mediators are drug targets in the treatment of allergic diseases, and hence understanding their interaction is likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 42 publications
3
40
1
2
Order By: Relevance
“…It has previously been suggested that nicotinic acid and nonivamide topical cream may modulate the activity of local immune cells, including granulocytes and TH 2 cells . However, our study identified no influence of this mechanism of enhancing capillary flow on either the local leucocyte subpopulations or granulocytic functional‐related surface antigen markers.…”
Section: Median Fluorescence Intensity (Au) For Granulocytes Monocytcontrasting
confidence: 65%
See 1 more Smart Citation
“…It has previously been suggested that nicotinic acid and nonivamide topical cream may modulate the activity of local immune cells, including granulocytes and TH 2 cells . However, our study identified no influence of this mechanism of enhancing capillary flow on either the local leucocyte subpopulations or granulocytic functional‐related surface antigen markers.…”
Section: Median Fluorescence Intensity (Au) For Granulocytes Monocytcontrasting
confidence: 65%
“…During allergy states, this prostanoid induces a vasodilatory response, increases vessel permeability, and mediates the activity of effector cells such as helper T cells, eosinophils, basophils, mast cells, and dendritic cells . Furthermore, in combination with cysteinyl leukotriene E 4 (LTE 4 ), PGD 2 is capable of altering adhesion, migration, and cytokine production by helper T cells …”
Section: Median Fluorescence Intensity (Au) For Granulocytes Monocytmentioning
confidence: 99%
“…PGD 2 has been shown to regulate apoptosis in a cell type specific manner. It protects Th2 cells from cytokine deprivation‐induced apoptosis via DP2 signaling, and antagonizes PGE 2 ‐mediated Bax activation and hence inhibits the induction of apoptosis in glioma cells . In contrast, PGD 2 induces apoptosis in human osteoclasts, leukemia cells and non‐small cell lung carcinoma cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PGD 2 has been recently shown to synergize with LTE 4 to stimulate diverse T H 2 functions and T H 2 cell and neutrophil crosstalk. 35,36 It is possible that during inflammation, LTD 4 plus PGE 2 treatment not only activates MCs and initiates inflammation, but also the product of this signaling, PGD 2 , can potentially perpetuate inflammation through combined action with LTE 4 . Both LTD 4 and PGE 2 have been demonstrated to phosphorylate Erk in MCs.…”
Section: Discussionmentioning
confidence: 99%